MULTIMEDIA PEMBELAJARAN UNTUK PENINGKATAN KREATIVITAS MELUKIS DI TAMAN KANAK-KANAK - Eny Munisah (Universitas Muhammadiyah Kotabumi, 2019)
Multimedia learning is very near with visual communication. The visualization of concept which is given to the learner as the conbination of pictur, diagram,graph, draft, and chart should become one. Creativity is the origin, suitable,and functional. The origin and the suittable painting of kindergarten is periodic,typology, and other.Painting of kindergarden is a pra-chart periode, while typology is visual and non visual type the indication who seldom appear with painting of children is stereotype, tranparant, lying down, perpendicular, and finanity. There are three creatives personality, they are: 1). open with experience, 2). the ability to evaluate situation based on standars of personality, 3). the ability to do experiment to play with concept. The condition above is used as basic toimprove the ability of kindergarten in peinting. They will play computer, painting, make a creative something if every person has three criterias above so he/she has a good psychology that will support to create a creative creation.